2014
DOI: 10.1007/s13197-014-1651-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the composition of unripe genipap (Genipa americana L.) fruit on the formation of blue pigment

Abstract: The physical and chemical characteristics of unripe genipap fruits and the proximate and amino acid compositions of the endocarp and mesocarp of the unripe fruits were determined, placing special emphasis on the possible role of the protein-amino acid fraction on the formation of the typical blue pigment of the matrix. The two parts of the fruit analyzed have low energy (49.88 kcal/100 g for mesocarp and 43.48 kcal/100 g for endocarp) and high fiber content (7.88 % for mesocarp and 16.76 % for endocarp). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…The color analyses showed that the extract (feed) was darker than the permeate, with lower tendency to green and yellow. Bentes et al (2015) evaluated the color of genipap fruit and observed similar color values for genipap mesocarp. The microfiltration membranes did not retain polyphenol and genipin compounds (no significant difference was detected in this case).…”
Section: Membrane Filtrations Of Genipap Extractmentioning
confidence: 76%
See 1 more Smart Citation
“…The color analyses showed that the extract (feed) was darker than the permeate, with lower tendency to green and yellow. Bentes et al (2015) evaluated the color of genipap fruit and observed similar color values for genipap mesocarp. The microfiltration membranes did not retain polyphenol and genipin compounds (no significant difference was detected in this case).…”
Section: Membrane Filtrations Of Genipap Extractmentioning
confidence: 76%
“…Genipap fruit has considerable concentrations of phytosterols, such as campesterol, stigmasterol, and β-sitosterol, which presents anti-obesity, antioxidant and antiproliferative functional properties (Bailao, Devilla, Conceicao, & Borges, 2015). Moreover, genipap contains an iridoid cross-linking compound named genipin, which forms a blue pigment by a spontaneous reaction with amine groups and has a great potential to be used by the food industry (Bentes, Souza, Amaya-Farfan, Lopes, & Faria, 2015). Proposition of processes for genipap pulp fruit processing is rarely reported in the literature, although the importance of this fruit had already been highlighted (Porto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2c ). According to Bentes et al ( 6 ), genipin is an aglycone, resulting from the hydrolysis of the geniposide, through the enzyme β-glucosidase.…”
Section: Resultsmentioning
confidence: 99%
“…This substance acquires high reactive potential with amine groups when exposed to oxygen, resulting in the formation of an intense blue pigment ( 3 ). Genipin is easy to extract because it has good solubility in water and hydroalcoholic solutions, which has contributed to its historically widespread use by indigenous peoples as a dye of utensils and for body pigmentation ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…A cor azul, oriunda da genipina (metabólito secundário) está presente também em outras partes da planta. Algumas atribuições da literatura para a espécie fazem referência a cor obtida do jenipapo: o suco do fruto verde ganha coloração azulada com a oxidação devido a reação entre a genipina e uma amina primária (SILVA et al, 2014;MERCADANTE, 2014;BENTES et al, 2015), sendo utilizado na pintura do corpo e de cerâmica pelos indígenas (LORENZI;MATOS, 2002;JESUS et al, 2015).…”
Section: Discussionunclassified